Analysis of the domestic list of otc medicines and development of approaches to its improvement - L. O. Hala; A. O. Chubai (The State Expert Center of the Ministry of Health of Ukraine, 2022)
In recent decades, every citizen tries for an active position regarding his own health. Such factors as improving the general level of medical literacy and quality of life of the population, developing of pharmaceutical market contribute to the spread of self-medication. The formation of the concept of responsible self-medication, which includes the free use by consumers of effective and safe over-the-counter (OTC) medicines has been the solution to the specified needs of society. The purpose of the study was to develop modern organizational approaches to the formation of the List of OTC medicines in Ukraine to ensure the proper level of pharmaceutical care. The objects of the study were the Lists of OTC medicines approved by orders of the Ministry of Health of Ukraine during 2010-2019; the register of medicines allowed to be dispensed without a prescription (according to the State Register of Medicines of Ukraine, as of February 2022); protocols of the pharmacist. The methods of marketing analysis, analytical-comparative, systematic, graphic and method of generalization were used. Based on the analysis of the Lists of OTC medicines valid in Ukraine in the relevant years (2010-2022), it was established that the number of OTC medicines and the specific weight of it in the registered drugs on the pharmaceutical market decrease annually (from 26.0% to 21.2%). According to the results of the comparative marketing analysis of the current List of OTC medicines (order of the Ministry of Health of Ukraine dated April 18, 2019 N 876) and the register of OTC medicines (according to the State Register of Drugs of Ukraine, as of February 2022), only insignificant differences were found in the distribution of assortment items by composition, ATC classification, countries of origin, dosage forms. Deficiencies of the current List of OTC medicines were identified, such as the presence of medicines with expired registration in 2019-2022; duplication of positions; the presence of trade names of the prescription group. According to the results of the research, organizational approaches that will contribute to the proper formation of the next edition of the domestic List of OTC medicines and its rational use by pharmacists and consumers to realize the possibilities of responsible self-medication are proposed. The results of the research can be used in the formation of a legal framework in Ukraine, which regulates the circulation of OTC medicines on the pharmaceutical market.